2020
DOI: 10.1209/0295-5075/130/46001
|View full text |Cite
|
Sign up to set email alerts
|

Intra-scales energy transfer during the evolution of turbulence in a trapped Bose-Einstein condensate

Abstract: In turbulence phenomena, including the quantum turbulence in superfluids, an energy flux flows from large to small length scales, composing a cascade of energy. It is a well-known fact that for multi-scale energy flow, dissipation can be scale-dependent. In particular, the existence of a range of scales where there is no energy accumulation, the inertial range, is an indication of universal behavior in turbulence. There are intrinsic difficulties associated with the measurement of the energy flux during the ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Hence, approaches other than the power-law behavior have been employed to overcome these issues. Energy and particle fluxes have been used in simulations [ 7 , 8 ] and experiments [ 9 , 10 ] as alternative methods to investigate and characterize quantum turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, approaches other than the power-law behavior have been employed to overcome these issues. Energy and particle fluxes have been used in simulations [ 7 , 8 ] and experiments [ 9 , 10 ] as alternative methods to investigate and characterize quantum turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the turbulent state can be identified and characterized in terms of the energy flux regardless of whether we employ the whole cloud or just a region close to the major axis of the expanded cloud. We should note that the axial trapping frequencies of this work and of Reference [11] are very close; however, in this work, we employ a radial trapping frequency that is ≈0.7 smaller than the one used in Reference [11]. Thus, the BECs in this work are much less elongated and closer to a spherical shape than the ones in Reference [11].…”
Section: Discussion and Final Remarksmentioning
confidence: 81%
“…This is because such large-scale inhomogeneities affect only regions in Fourier space up to the order of k ∼ 2π/L min , where L min is the smaller linear size of the cigar-shaped cloud. In a previous work [11], we studied the impact of anisotropy in the energy transfer during the evolution of turbulence in a trapped BEC. Like the integral length scale, the energy flux can also be computed from the kinetic energy spectrum.…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some inherent challenges in determining and characterizing the turbulent state in these systems [14,15]. Hence, different approaches have been used to clarify aspects of quantum turbulence [114][115][116]. What we showed in Section 3 can be used to look at the phenomena from a different perspective, which is of paramount importance when dealing with quantum turbulence.…”
Section: Discussionmentioning
confidence: 99%